Expression of Structural Flavonoid Biosynthesis Genes in Dark-Blue and White Myrtle Berries (Myrtus communis L.) - Medda, Silvia (Plants (Basel), 2021)
Within the myrtle (Myrtus communis L.) species, different genotypes may produce dark-blue berries or white berries depending on the peel color upon ripening. One dark-blue cultivar and one white myrtle cultivar were used to study the molecular mechanisms underlying flavonoid biosynthesis. The relative expression levels of common (PAL, CHS, CHI, DFR and LDOX) and specific (FLS, ANR, LAR and UFGT) flavonoid genes were analyzed during fruit development by means of quantitative real-time polymerase chain reaction (RT-qPCR). Moreover, the anthocyanin content was determined, and it showed an increase with the ripening of the berries of the dark-blue cultivar. The results showed an increased transcript abundance of PAL, CHI, DFR, LDOX and UFGT gene expression in the dark-blue cultivar compared to the white one, as well as a strong positive correlation between the changes in gene expression and anthocyanin accumulation. The transcript levels of UFGT showed sharp increases at 150 and 180 days after full blooming (DAF) in the dark-blue cultivar, which corresponded with anthocyanin accumulation. However, ripening seemed to modulate the expression of genes implicated in flavonols (i.e., FLS) and flavan-3-ols (i.e., LAR and ANR) in different manners. However, whereas FLS transcript accumulation increased at the end of the ripening period in the dark-blue cultivar, LAR and ANR gene expression decreased in both cultivars.